Why Only Efficiency, and Not Efficacy, Matters in Psychotherapy Practice - Berg, Henrik (Frontiers in Psychology, 2021)
Evidence-based practice in psychology consists of two quality parameters. One of these parameters is efficacy and the other is efficiency. In this paper, it is argued that the only relevant parameter for determining quality in clinical care is efficiency. It is argued that emphasising efficacy in psychotherapy practice is symptomatic of a scientocentric ideal in evidence-based practice in psychology. The proper understanding and use of scientific findings depend on leaving this scientocentric ideal. Crucially, efficiency must be related to the ethical aims integrated in a practice like psychotherapy.